DEVELOPING OF INTERACTIVE MULTIMEDIA FOR THE LEARNING OF OLD LITERATURE READING BASED ON RESEPTION THEORY FOR JUNIOR HIGH SCHOOL STUDENTS - Kusyani, Diah; Syamsi, Kastam (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study aims to develop interactive multimedia for the learning of old literature reading based on reception theory that acceptable as a learning media or high school students.This study is Research and Development (R & D) research by using Borg & Gall model. This study has been modified into six research steps namely, preliminary stage, product planning, product development, validation test, product revision, and product trial. The subjects consisted of 3 students for one-to-one trials, 6 students for small group trials, and 25 students for large group trials. The result of the research shows that (1) the interactive multimedia of reading old literature reading based on reception theory for junior high school students is categorized as "good" according to expert opinion, and "excellent" category based on media expert, teacher response, small group trials, and large group trials. (2) interactive multimedia learning reading of old literature based on reception theory for junior high school students is suitable for learning media.